Determination of mechanical properties of intra-layer abaca–jute–glass fiber reinforced composite - Vijaya Ramnath, B.; Manickavasagam, V.M.; Elanchezhian, C.; Vinodh Krishna, C.; Karthik, S.; Saravanan, K. (Materials in engineering, 2014)
•Composites are fabricated with jute and abaca fibers.•Fibers are arranged in different orientations.•Effects of varying proportions of fibers are studied.•Investigation on mechanical properties is done.•Failure morphology analysis is done using SEM. Composites made with natural fibers are finding applications in a wide variety of engineering fields due to their low cost and eco-friendly nature. This paper deals with the fabrication and evaluation of hybrid natural fiber composite using jute and abaca fibers along with glass fibers. Each composite is made up of five layers with three layers of jute and abaca enclosed by two layers of glass fibers. The composites are manufactured with three different fiber orientations and the compositions are varied in three different proportions. The fabricated composite samples are tested to investigate their various mechanical properties. From the test results, it is observed that fiber orientation plays a vital role in determining the mechanical properties of the composite. Morphological analysis is done using Scanning Electron Microscope (SEM).